2014
DOI: 10.1016/j.jaci.2014.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Basophil activation test discriminates between allergy and tolerance in peanut-sensitized children

Abstract: BackgroundMost of the peanut-sensitized children do not have clinical peanut allergy. In equivocal cases, oral food challenges (OFCs) are required. However, OFCs are laborious and not without risk; thus, a test that could accurately diagnose peanut allergy and reduce the need for OFCs is desirable.ObjectiveTo assess the performance of basophil activation test (BAT) as a diagnostic marker for peanut allergy.MethodsPeanut-allergic (n = 43), peanut-sensitized but tolerant (n = 36) and non–peanut-sensitized nonall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
335
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(372 citation statements)
references
References 33 publications
26
335
1
10
Order By: Relevance
“…Further repertoire analysis of CD4+ T cells during IT may reveal the preferential deletion or reprogramming of T cells based on factors like functional avidity or structural TCR avidity. Additionally, several IT studies, particularly for allergy, have identified changes in antigen-specific IgE and IgG responses, regulatory B cells, and basophils associated with tolerance induction (13,17,39,46,51).…”
Section: Discussionmentioning
confidence: 99%
“…Further repertoire analysis of CD4+ T cells during IT may reveal the preferential deletion or reprogramming of T cells based on factors like functional avidity or structural TCR avidity. Additionally, several IT studies, particularly for allergy, have identified changes in antigen-specific IgE and IgG responses, regulatory B cells, and basophils associated with tolerance induction (13,17,39,46,51).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 CD203c can be rapidly measured by flow cytometry and has been proposed as a diagnostic tool in atopic disease, including peanut, drug and wasp venom allergy. [20][21][22] It has been shown that basophils are primed and hyper-responsive to Af allergen stimulation in CF-ABPA. 18 In this current study, BAT to Af was employed to identify Af sensitization in a CF cohort and it was correlated with key CF clinical measurements.…”
Section: Abbreviationsmentioning
confidence: 99%
“…By an in‐vitro dose‐response allergen stimulation of the basophils, their allergen threshold sensitivity, CD‐sens 16 can be accurately determined. Studies have shown that CD‐sens correlates significantly with bronchial allergen threshold sensitivity 9 , nasal allergen challenge 14, 18 , and oral food challenge 15, 19, 20 .…”
Section: Discussionmentioning
confidence: 99%